Triple T pattern on ECG and Apical Hypertrophic Cardiomyopathy - Khaled, Md Fakhrul Islam; Islam, Md Azharul; Salim, Md Abu; Rahman, Md Mukhlesur; Haque, Mostashirul; Chawdhury, MSI Tipu; Emran, Mohammed; Rahman, Md Walidur; Adhikary, Dipal Krishna (KYAMC Journal, 2019)
T wave on ECG is the positive deflection after QRS complex which reflect the ventricular repolarization. The amplitude of T wave is 5mm in limb lead and 10mm in chest leads. T wave is upright in all leads except a VR and V1, but it may be inverted in V1-V3 in pediatric age group. Triple T pattern is the negative T waves in inferior leads, anterior leads and on a VR. Triple T pattern is a very common finding in Apical hypertrophic cardiomyopathy (AHCM). Apical hypertrophic cardiomyopathy is a rare form of cardiomyopathy that affects LV apex and rarely RV apex or both. Patients with AHCM has a wide range of presentations, ranging from asymptomatic to palpitation, nonspecific chest discomfort, chest pain etc. It does not present with features which are common in other type of obstructive hypertrophic cardiomyopathy like presyncope, syncope, and it has less chance of sudden cardiac death. First clue of diagnosis of AHCM is widespread negative T wave in ECG. Although negative T-waves may be found in chest leads in 93% of cases. Cardiovascular magnetic resonance (CMR) is the best diagnostic tool. Proper transthoracic echocardiographic evaluation demonstrates apical wall thickness >15 mm and a ratio of maximal apical to posterior wall thickness >1.5 mm. Beta-blockers are mainstay of treatment whereas implantable cardioverter defibrillator (ICD) is recommended for high risk cases. As it is a genetic disease genetic counseling and periodic follow up is required. KYAMC Journal Vol. 10, No.-3, October 2019, Page 160-163